After the pop-up games: London's never-ending regeneration. (June 2015) - Vijay, Ameeth
This paper examines the temporality of urban planning in contemporary London, especially with regard to the 2012 Olympic Games. I argue that planners and officials deployed a rhetoric of permanence to validate not only the Games themselves, but also the costly development and infrastructural changes in the city as well as human displacements. Specifically, a decentralized network of planners, officials, consultants, and administrators used temporal concepts such as 'legacy', 'sustainability', and 'regeneration' in describing the benefits of hosting the Games, all of which purposely ignored the temporary and unsustainable nature of the two-week sporting event. I further argue that this rhetoric could be sustained only through an implication that the Olympic site—and East London as a whole—was in a state of ruin, a state which could be ameliorated through the production of this sporting 'mega-event'. Above all, the Olympics attempt to rhetorically mitigate their own temporary, 'pop-up' quality for the sake of an urban settler colonialism.